2022
DOI: 10.3390/pr10020429
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sparger Type on Mass Transfer in a Pilot-Scale Internal Loop Airlift Reactor

Abstract: In a pilot-scale internal loop airlift reactor with a height of 5.5 m and a main column diameter of 0.484 m, the influence of three gas sparger structures (ladder distributor, tri-nozzle sparger and perforated plate) on the volumetric mass transfer coefficient kLa was investigated. It was found that the perforated plate produces the highest gas holdup difference and circulating liquid velocity between the riser and the downcomer. The perforated plate provides the most efficient mass transfer due to the more un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Naidoo et al and Wang et al found that in the pilot-scale external loop ALRs, the bubble size decreased as the diameter of the pores of the perforated plate decreased. [48,49] Additionally, with smaller bubbles, the gas holdup increased and mass transfer performance improved. Ham et al found that fine sand and coarse sand diffusers can promote the mass transfer in an ALR owing to the small bubbles having long residence time.…”
mentioning
confidence: 99%
“…Naidoo et al and Wang et al found that in the pilot-scale external loop ALRs, the bubble size decreased as the diameter of the pores of the perforated plate decreased. [48,49] Additionally, with smaller bubbles, the gas holdup increased and mass transfer performance improved. Ham et al found that fine sand and coarse sand diffusers can promote the mass transfer in an ALR owing to the small bubbles having long residence time.…”
mentioning
confidence: 99%
“…The radial positions were at the center and sidewall inside the reactor. The detailed experimental steps can be obtained from our previous research work [31]. Since temperature also has a significant impact on k L a, when the ambient temperature changes, correction can be performed using the following equation [32][33][34]:…”
Section: Experimental Workmentioning
confidence: 99%
“…The two-stage had better performance improvement. Then, Wang et al [18] studied the hydrodynamic characteristics, mass transfer, and mixing performance of three different reactors, a bubble column reactor, a single-stage internal loop airlift reactor, and a four-stage internal loop airlift reactor. The transfer performance of the four-stage is better than the other two.…”
Section: Introductionmentioning
confidence: 99%